2021
DOI: 10.3171/2020.10.peds20633
|View full text |Cite
|
Sign up to set email alerts
|

Targeting accuracy of robot-assisted deep brain stimulation surgery in childhood-onset dystonia: a single-center prospective cohort analysis of 45 consecutive cases

Abstract: OBJECTIVE Deep brain stimulation (DBS) is an established treatment for pediatric dystonia. The accuracy of electrode implantation is multifactorial and remains a challenge in this age group, mainly due to smaller anatomical targets in very young patients compared to adults, and also due to anatomical abnormalities frequently associated with some etiologies of dystonia. Data on the accuracy of robot-assisted DBS surgery in children are limited. The aim of the current paper was to assess the accuracy of robot-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The use of interventional MRI-guided DBS using a skull-mounted aiming device in conjunction with dedicated software, which is independent of physiological testing, showed good accuracy and comparable outcomes in pediatric dystonia [29, 61]. Robot-assisted stereotactic implantation may have even greater accuracy [62].…”
Section: Surgical Considerations In Pediatric Dbsmentioning
confidence: 99%
“…The use of interventional MRI-guided DBS using a skull-mounted aiming device in conjunction with dedicated software, which is independent of physiological testing, showed good accuracy and comparable outcomes in pediatric dystonia [29, 61]. Robot-assisted stereotactic implantation may have even greater accuracy [62].…”
Section: Surgical Considerations In Pediatric Dbsmentioning
confidence: 99%
“…Rehabilitation and medical management along with local botulinum toxin injections are the treatment of choice in focal dystonia ( Albanese and Lalli, 2012 ; Ehrlich and Frucht, 2016 ). Since segmental and generalized forms of dystonia may not respond well to pharmacological therapies, there has been growing interest and expansion in the application of bilateral neuromodulation of deep brain structures in the management of these challenging conditions ( Zittel et al, 2009 ; Martínez et al, 2014 ; Shaikh et al, 2014 ; Fox and Alterman, 2015 ; Tambirajoo et al, 2020 ; Furlanetti et al, 2021 ). ATD is more frequently reported in the context of severe segmental and generalized dystonic syndromes, and rarely as an isolated presentation of dystonia ( Bhatia et al, 1997 ; Benecke and Dressler, 2007 ; Albanese et al, 2013 ; Lizarraga and Fasano, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…7,[24][25][26] Three studies (including this study) reported the use of a floor-mounted robot with a frameless transient fiducial array, with a target radial error of 0.84 ± 0.54 mm (n = 631 electrodes), operative time of 182.4 ± 47.8 minutes (n = 315), and total procedure time of 311.9 ± 63.0 min (n = 315). 27,28 One study reported their use of a floormounted robot with optical registration, and the only metric recorded was target radial error: 1.28 ± 0.37 (n = 60 electrodes). 29 Our meta-analysis found that the floor-mounted systems are more accurate, with a radial target error of 0.90 ± 0.46 mm (n = 1510 electrodes), compared with skull-mounted systems (1.12 ± 0.54 mm, n = 406) (P = .028).…”
Section: Meta-analysismentioning
confidence: 99%